INTO THE DEPTHS OF THE HUMAN SOUL. AN OUTLINE OF PROTECTORATE PSYCHOLOGICAL PROSE - Šidáková Fialová, Alena (Bohemica Olomucensia, 2021)
The study deals with the problems of the Protectorate psychological prose, its form and changes in the period 1939-1945. It first characterizes general tendencies and backgrounds, then discusses individual authors. It describes the top works of the period, i.e. the novels of Václav Řezáč and Jan Drda. It then describes a group of works that focus on exceptional characters, artists and doctors. Among the best known are Karel Schulz's The Stone and the Pain, and among the lesser known are the works of K. J. Beneš, Čestmír Jeřábek, Helena Dvořáková and others. Another section is devoted to specific works by younger authors such as Bohuslav Březovský, Vladimír Pazourek or Miroslav Hanuš. They are united by the figure of a young man suffering for love, loneliness and the search for the meaning of life. A large part of the Protectorate's prose consisted of works dealing with interpersonal relationships, especially marital and lover's relationships (Václav Řezáč, Jarmila Glazarová, František Kožík, Olga Barényiová). Interpersonal relationships on the background of small-town life were the subject of several novels by Jaroslav Havlíček, and the work of Vladimír Neff also stands out from contemporary production.
Keywords: Protectorate; psychological prose; Jaroslav Havlíček; Václav Řezáč